Habitual Ethics? - Delacroix, Sylvie (Bloomsbury Academic, 2022)
What if data-intensive technologies' ability to mould habits with unprecedented precision is also capable of triggering some mass disability of profound consequences? What if we become incapable of modifying the deeply-rooted habits that stem from our increased technological dependence? On an impoverished understanding of habit, the above questions are easily shrugged off. Habits are deemed rigid by definition: 'as long as our deliberative selves remain capable of steering the design of data-intensive technologies, we'll be fine'. To question this assumption, this open access book first articulates the way in which the habitual stretches all the way from unconscious tics to purposive, intentionally acquired habits. It also highlights the extent to which our habit-reliant, pre-reflective intelligence normally supports our deliberative selves. It is when habit rigidification sets in that this complementarity breaks down. The book moves from a philosophical inquiry into the 'double edge' of habit - its empowering and compromising sides - to consideration of individual and collective strategies to keep habits at the service of our ethical life. Allowing the norms that structure our forms of life to be cotton-wooled in abstract reasoning is but one of the factors that can compromise ongoing social and moral transformations. Systems designed to simplify our practical reasoning can also make us 'sheep-like'. Drawing a parallel between the moral risk inherent in both legal and algorithmic systems, the book concludes with concrete interventions designed to revive the scope for normative experimentation. It will appeal to any reader concerned with our retaining an ability to trigger change within the practices that shape our ethical sensibility. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the Mozilla Foundation.